2021
DOI: 10.1108/gkmc-09-2020-0136
|View full text |Cite
|
Sign up to set email alerts
|

WeChat usage during COVID-19 pandemic lockdown: the mediating role of online self-disclosure on quality of friendship and well-being

Abstract: Purpose The purpose of this paper is to investigate university students’ WeChat usage during the COVID-19 pandemic lockdown in relation to the mediating role of online self-disclosure on their quality of friendship and well-being. A model is proposed to explain how students’ interactions occur during the lockdown and the mediatory role which self-disclosure plays in influencing their socio-psychological markup. Design/methodology/approach The research model was tested empirically through a survey conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Graduate research students are students cohort who are confronted with various academic challenges such as balancing academic, personal, and family life (Virtanen et al, 2017). As a result, they require specific psychological well-being and self-care mechanism for reducing anxiety and increasing psychological capability (Amosun, Jianxun, et al, 2022). An example of such is mindfulness training which has been demonstrated to significantly lower psychological anxiety among university students in different ways (Barry et al, 2019;Bellinger et al, 2015;Charoensukmongkol, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Graduate research students are students cohort who are confronted with various academic challenges such as balancing academic, personal, and family life (Virtanen et al, 2017). As a result, they require specific psychological well-being and self-care mechanism for reducing anxiety and increasing psychological capability (Amosun, Jianxun, et al, 2022). An example of such is mindfulness training which has been demonstrated to significantly lower psychological anxiety among university students in different ways (Barry et al, 2019;Bellinger et al, 2015;Charoensukmongkol, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As youth heavily rely upon CMC for connecting with friends (Kircaburun et al, 2020) and social anxiety is most prevalent during young adulthood (Jefferies & Ungar, 2020), understanding the conditions in which online self-disclosure may support those with high social anxiety is especially relevant for young adults. According to the extant literature, personal information shared with others in dyadic and masspersonal CMC increases social connectedness and in turn enhances subjective well-being (Amosun et al, 2021;D. Liu et al, 2019;Utz, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences for disclosure, enhanced online self-disclosure has been associated with greater feelings of connectedness across the different communication modes, albeit to varying degrees (D. Liu et al, 2019). That is, positive associations were observed when users conversed in relatively private online contexts (Amosun et al, 2021), or more publicly on social networking sites (Utz, 2015) and blogging sites (Z. Liu et al, 2016).…”
Section: Social Benefits Associated With Positive Online Self-disclosurementioning
confidence: 99%
“…The information could be text, image, audio, video, or geographic location. Some studies have demonstrated that social media are indeed effective and efficient in promoting the quality of friendship by assisting students to build on existing relationships and make new friends during crisis periods, such as during the COVID-19 pandemic lockdown (Chen, 2015 ; Wen et al, 2016 ; Amosun et al, 2021 ). Therefore, digital interactions supported by trust in the context of globalized risk should be one of the focuses of research in computer-mediated communication.…”
Section: Introductionmentioning
confidence: 99%